Leadersrhip patterns of high schhol principals and their impact on the career level of physical education teachers - CHETOUH, MEROUANE (sports creativity, 2023)
We seek through this modest work to study one of the most important topics in the field of school management and its outputs through a wise educational leadership with continuous effectiveness contribute to reach the desired goals, including job satisfaction, so the study looked at the degree of satisfaction of career teachers of physical education and sports through The nature of the interaction between school principals and teachers who may contribute to their satisfaction with work depends largely on the leadership style used by school principals and their suitability for each position of the work situation.